Sleep Alterations and Cognitive Decline - Lucey, Brendan P. (Seminars in Neurology, 2025)
Sleep disturbances and cognitive decline are intricately connected, and both are prevalent in aging populations and individuals with neurodegenerative disorders such as Alzheimer's disease (AD) and other dementias. Sleep is vital for cognitive functions including memory consolidation, executive function, and attention. Disruption in these processes is associated with cognitive decline, although causal evidence is mixed. This review delves into the bidirectional relationship between alterations in sleep and cognitive impairment, exploring key mechanisms such as amyloid-β accumulation, tau pathology, synaptic homeostasis, neurotransmitter dysregulation, oxidative stress, and vascular contributions. Evidence from both experimental research and population-based studies underscores the necessity of early interventions targeting sleep to mitigate risks of neurodegenerative diseases. A deeper understanding of the interplay between sleep and cognitive health may pave the way for innovative strategies to prevent or reduce cognitive decline through improved sleep management.
Keywords: cognition; sleep; sleep disorders; aging; neurodegeneration